Analysis of Gender and Scientific Output of Researchers in the Spanish University - Ras-Carmona, Alvaro; Lafuente, Esther M.; Reche, Pedro A. (Journal of Education Culture and Society, 2025)
Aim. Promoting gender equality and excellence are key policies in academia. Therefore, in this work, we investigated scientific output and potential gender disparities of researchers across different faculty positions in the Complutense University of Madrid (UCM), the largest academic institution in Spain.Methods. Researchers’ data were obtained from the UCM Scientific Production Portal. Full name, academic rank, affiliation, thesis defence year and SCOPUS Hirsch (h)-index was collected for each researcher. Sex (men/women) of researchers was assigned after their first names using Python programming. The m-index was computed by dividing the h-index between the length of the researcher´s career, taking in consideration the first publication. Statistical comparisons and analyses were carried out in RStudio.Results. We found that women are clearly underrepresented in full professor positions despite being a majority in lower academic ranks. This gender disparity in full professor positions is however narrowing down in recent years. The scientific output of researches, as judged by the h-index, varied greatly between Faculties, but overall, correlated positively with the academic rank and no significant differences were detected between women and men, although exceptions were noted. Judging by the m-index, the scientific output of women and men in full professor positions were also alike.Conclusion. There is effective equality between genders within UCM faculty ranks.